Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov. - Makarchenko, Eugenyi A. (Zootaxa, 2019)
Illustrated description of the adult male of Pagastia (P.) subletteorum sp. nov., redescription of the pupa and adult male of P. (P.) orthogonia Oliver and P. (P.) partica (Roback), with redescription of the adult male of P. (Hesperodiamesa) sequax (Garrett) from North America are provided. An emended generic diagnosis and a key to determination of adult males of all known species of Pagastia Oliver are also provided.